Genetic Variability in Bitter Gourd (Momordica charantia L.) - Murlee Yadav (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2008)
The variance analysis for 17 plant characters showed significant differences. Maximum vine length was recorded in IC-85635A. Significantly higher number of primary branches per vine and internodal length were observed in IC-85639. Maximum number of nodes was observed in JMC-4. Significantly minimum number of days for first appearance of male flower and maximum fruit length, fruit width, yield per vine, yield per plot, yield/ha were recorded in MC-84. Highest number of fruits per vine was recorded in GY-I and minimum powdery mildew infestation was observed in JMC-22.